UPAYA PEMERINTAH DALAM MELESTARIKAN URBAN HERITAGE DALAM MENDUKUNG LIVEABLE CITY KOTA YOGYAKARTA - Fahril Fanani; Ayu Candra Kurniati (KURVATEK, 2018)
Cultural heritage has values on the past cultural heritage that must be preserved and maintained in order to support urban development in the future. The city of Yogyakarta has been appointed as one of the "Liveable Cities" in Indonesia (IAP, 2014) in terms of preservation of cultural heritage. Based on the Government Regulation of Daerah Istimewa Yogyakarta No. 40/2014 in terms of “Determaning Cultural Heritage Areas”, stated that Yogyakarta has 5 (five) Cultural Heritage Areas (KCB) which are: Kraton, Kotabaru, Pakualaman, Malioboro and Kotagede. The purpose of this study is to identify the government's efforts to preserve the Yogyakarta cultural heritage building in terms of maintaning the Liveable City Index of Yogyakarta. Next, collecting data method is using observation, interviews and literature studies. The research method is a qualitative descriptive approach, by using preservation variables considering with liveable city criteria, such as: protection, development and utilitation of cultural heritage buildings. Furthermore, the results is the Yogyakarta`s government has prepared conservation guidelines and management of cultural heritage buildings for each cultural heritage area, but those guidelines and management are not integrated with the governor's regulation. The conclusion obtained is the lack of integration from several policies / regulations set by the government in the preserving of cultural heritage buildings